Household Food Insecurity, Local Food Environment Measures and Obesity in Adult Women in Hermosillo, México (P04-044-19) - García-López, Zahid (Curr Dev Nutr, 2019)
OBJECTIVES: To examine the relationship between prevalence of overweight and obesity in adult women, household food insecurity (FI) and local food environment measures in Hermosillo, Mexico. METHODS: We conducted a cross-sectional study design with a multi-stage sampling process for neighborhoods, households and individuals (in areas with medium and high levels of social marginalization). Measures of body weight, height and waist circumference from adult women were collected from September to November 2018. Through validated questionnaires and face-to-face interviews, we assessed food security (scale of food security for families in northwestern Mexico), perception of the local food environment (NEMS-P), socioeconomic status and self-reported physical activity. RESULTS: Prevalence of overweight and obesity among women was 80.5%, 82% were moderately active, and 69% did mainly housework. Seventy nine % of households showed some level of FI. Participants reported mainly supermarkets and corner stores for food purchasing (75.7% and 15.4%, respectively). There was a higher probability of obesity in women who visited neighborhood corner stores daily compared to those who purchased in other food establishments (OR: 3.66; 95% CI, 1.2–10.4). Among households with FI, the consumption of food while watching television, occupation, cohabitation status (being married or living with a partner) and the frequency and places of food purchasing, were associated with women´s overweight or obesity (P < 0.05). There was an association between women's waist circumference and severe household FI (P < 0.05). CONCLUSIONS: The food environment and household FI were related to the prevalence of overweight and obesity among adult women. FUNDING SOURCES: This research was funded by the Interdisciplinary Research Network on Obesity Prevention at Centro de Investigación en Alimentación y Desarrollo.